"The Influence of Sustainability Initiatives on Brand Loyalty: A Study of Consumer Perceptions in the FMCG Sector" - M. Shireesha, A. Madhuri, S. Melchior Reddy, B. R. Kumar (Journal of Informatics Education and Research, 2024)
This study explores the impact of sustainability initiatives on brand loyalty within the Fast-Moving Consumer Goods (FMCG) sector, focusing on consumer perceptions. As environmental concerns continue to rise, companies are increasingly adopting sustainability practices to enhance their brand image and consumer engagement. This research aims to understand the extent to which these initiatives influence consumer loyalty. Utilizing a mixed-methods approach, the study gathers data through surveys and interviews from a diverse sample of consumers across different demographics. The findings reveal a positive correlation between perceived sustainability efforts and brand loyalty, with a significant number of consumers indicating a preference for brands that align with their environmental values. Furthermore, the study identifies key factors that mediate this relationship, including brand transparency, the authenticity of sustainability claims, and the perceived impact of these initiatives on the environment. The results suggest that brands in the FMCG sector can strengthen consumer loyalty by effectively communicating their sustainability efforts and ensuring that these initiatives are genuine and impactful. This research contributes to the growing body of literature on sustainable marketing and provides practical insights for brands seeking to enhance consumer loyalty through sustainability. Future research should explore the long-term effects of sustainability initiatives on brand loyalty and examine the role of cultural and regional differences in consumer perceptions.